National Legal Development and the Rule of Law: A Comparative Study of Indonesian and South African Law - Pratama, Amardyasta Galih (LEGAL BRIEF, 2025)
Indonesia and South Africa are both countries that adhere to the principle of the rule of law, where the state is bound by and subject to the law. However, despite the similarity of this principle, the two countries show significant differences in how they conceptualize and formulate their constitutions, mainly due to their different historical, political and socio-cultural backgrounds. The main issue addressed in this research is how these different national contexts influenced the development and implementation of the constitutional rule of law in each country. This research aims to analyse the constitutional development of Indonesia and South Africa by examining the underlying philosophy, historical trajectory and structural design of each country's constitution. Using a historical and comparative approach, this research employs a literature review and descriptive qualitative methods to explore how the rule of law is embedded and operationalized in each constitutional system. The research seeks to show that the unique national experiences of Indonesia and South Africa played an important role in shaping their respective constitutional frameworks, and that these experiences influence how the rule of law is understood and implemented in practice